Species-Specific Antimonial Sensitivity in Leishmania Is Driven by Post-Transcriptional Regulation of AQP1 - Mandal, Goutam; Mandal, Srotoswati; Sharma, Mansi; Charret, Karen Santos; Papadopoulou, Barbara; Bhattacharjee, Hiranmoy; Mukhopadhyay, Rita (PLOS Neglected Tropical Diseases, 2015)
Author Summary The degree of response to antimonial drugs varies widely between species and even among strains of the same species of the protozoan parasite Leishmania. However, the molecular mechanism(s) is unknown. In this study, we show that Leishmania aquaglyceroporin AQP1 drives this species-specific antimonial resistance. Aquaglyceroporins are channel proteins that facilitate the passage of small uncharged molecules, such as glycerol and water, across the biological membranes. AQP1 helps the parasite cope with the osmotic challenges it faces during its life cycle. Additionally, AQP1 is an adventitious facilitator of antimonite, the active form of pentavalent antimonial drugs. We show that AQP1 expression level is species-specific, and less AQP1 in visceral species compared to the cutaneous species results in increased resistance to antimonials. We also demonstrate that the 3’-untranslated regions (3’-UTR) of the AQP1 mRNA is a major determining factor of species-specific regulation of AQP1. Along with water homeostasis, aquaglyceroporins are also involved in directed cell migration. The variable levels of AQP1 in different Leishmania species may enable them to find their appropriate niches in vertebrate hosts and cope with the species-specific osmotic challenges during their life cycles.